A potential drug interaction between phenobarbital and dolutegravir: A case report. Issue 6 (June 2018) - Hikasa, Shinichi; Sawada, Akihiro; Seino, Hitomi; Shimabukuro, Shota; Hideta, Kyoko; Uwa, Noriko; Higasa, Satoshi; Tokugawa, Tazuko; Kimura, Takeshi
Abstract: In this report, we describe a human immunodeficiency virus (HIV)-infected patient in whom changes in phenobarbital (PB) dosage resulted in associated changes in plasma concentrations of dolutegravir (DTG). His plasma concentrations of DTG were 0.934, 0.584, 1.003 and 3.25 μg/mL, respectively, with concomitant daily PB doses of 40, 70, 30 and 0 mg, respectively. This case suggests that PB can lead to a remarkable reduction in the plasma concentration of DTG in a dose-dependent manner.